Revealed Standards for Distributing Public Home-Care on Clients - Audun Langørgen (Statistics Norway, Research Department, 2000)
When private goods are publicly provided at subsidized prices, government authorities have to determine the distribution of services on recipients. Such distributions are commonly based on legal regulations and professional guidelines. Thus governments are assumed to develop service standards that are incorporated in the preferences for allocation of services. The purpose of this paper is to analyse the behavior of local governments when they are allocating home-care services on elderly and disabled clients. Based on Norwegian data it is demonstrated that service standards as well as economic constraints have an impact on the supply of home-care. As expected the supply to individual clients increases with the degree of disablement. The model estimates also show that service standards vary substantially between different client groups. For instance, service levels for mentally retarded are rather high compared to elderly clients in non-single households. Individual service standards are derived from observed behavior by means of model simulation, where the standards are defined for an average level of municipal incomes and prices. The results are used to evaluate the degree of mismatch between service supply and common service standards in different local communities.
Keywords: H42; H72; I18; 330; Local public finance; care for the elderly and disabled; service production standards